Mindfulness dalam Perspektif Neuropsikologi: Analisis Bibliometrik - Nandiwardana, Antonius (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2024)
Mindfulness is gaining prominence in academic community particularly in neuropsychology. This research aims to conduct a bibliometric analysis of neuropsychology and brain research on mindfulness. 929 documents from Scopus database were analyzed with Bibliometrix software. The retrieved data regarding institutions, journal titles, countries, authors, and keywords. The analysis is focused on the research trend, the performance, and the collaboration network. The result indicates that neuropsychology and brain research on mindfulness were conducted from 1994 – 2023. The highest peak in the total production of neuropsychology research articles on mindfulness is 2022 with 142 documents. In addition, the data shows that certain authors, countries, and institutions contribute greatly to neuropsychology research on mindfulness. There are social interactions among authors, institutions, and countries. Future trends in this area of research will focus on topics related to depression, meditation, psychotherapy, and executive function. The results of this study provide insight into the growing trends in neuropsychology studies on mindfulness and data to assist researchers in identifying research gaps.